US CIVIL WAR MENURUT FORREST CARTER - Sudiro, Suryo; Abdul Karim, Sayit; Juhansar, Juhansar (Adabiyyāt: Jurnal Bahasa dan Sastra, 2020)
A novel may reflect the political interests and actions of the author. The author can make a story that is purposed to alter common consciousness. This article uses historicism as an interpretation theory. Historicism is used to avoid careless interpretation. With historicism, the story written in the novel is matched with historical events written in some history books. Forrest Carter writes a lot about US Civil War. He, in purpose, does not write about slavery that is commonly read as the cause of the US Civil War. He writes a lot about the murder of women and children by the northern US army soldiers in southern districts. He also writes a lot about the cooperation of his white character with a Cherokee. Above all written by Forrest Carter, the influence of his life and his political interests are seen.